Application of Stem Cells in Stroke: A Multifactorial Approach - Singh, Manisha; Pandey, Pranav K.; Bhasin, Ashu; Padma, M. V.; Mohanty, Sujata (Frontiers in Neuroscience, 2020)
Stroke has a debilitating effect on the human body and a serious negative effect on society, with a global incidence of one in every six people. According to the World Health Organization, 15 million people suffer stroke worldwide each year. Of these, 5 million die and another 5 million are permanently disabled. Motor and cognitive deficits like hemiparesis, paralysis, chronic pain, and psychomotor and behavioral symptoms can persist long term and prevent the patient from fully reintegrating into society, therefore continuing to add to the costly healthcare burden of stroke. Regenerative medicine using stem cells seems to be a panacea for sequelae after stroke. Stem cell-based therapy aids neuro-regeneration and neuroprotection for neurological recovery in patients. However, the use of stem cells as a therapy in stroke patients still needs a lot of research at both basic and translational levels. As well as the mode of action of stem cells in reversing the symptoms not being clear, there are several clinical parameters that need to be addressed before establishing stem cell therapy in stroke, such as the type of stem cells to be administered, the number of stem cells, the timing of dosage, whether dose-boosters are required, the route of administration, etc. There are upcoming prospects of cell-free therapy also by using exosomes derived from stem cells. There are several ongoing pre-clinical studies aiming to answer these questions. Despite still being in the development stage, stem cell therapy holds great potential for neurological rehabilitation in patients suffering from stroke.